Shockwave treatment for medial tibial stress syndrome in athletes; a prospective controlled study - Moen, M. H.; Rayer, S.; Schipper, M.; Schmikli, S.; Weir, A.; Tol, J. L.; Backx, F. J. G. (British Journal of Sports Medicine, 2012)
Objective - The purpose of this study was to describe the results of two treatment regimens for medial tibial stress syndrome (MTSS); a graded running programme and the same running programme with additional shockwave therapy (extracorporeal shockwave therapy; ESWT).